Hydrotherapy in Advanced Heart Failure: the Cardio-HKT Pilot Study - Municinó, Annamaria; Nicolino, Annamaria; Milanese, Manlio; Gronda, Edoardo; Andreuzzi, Bruno; Oliva, Fabrizio; Chiarella, Francesco (Monaldi Archives for Chest Disease, 2016)
Background: In-water exercise, hydrotherapy, may offer an attractive alternative to conventional training in markedly compromised patients with advanced HF. This Pilot Study evaluates the safety and efficacy of Cardio-Hydrokinesitherapy (Cardio-HKT) in patients with advanced HF on optimal medical therapy. Cardio-HKT is a novel rehabilitation program that includes training sessions in warm water (31°C), integrated by educational and psycho-behavioural sessions to promote healthy life style modifications. Methods: We studied 18 adult patients with advanced HF, LVEFII and peak oxygen uptake (peak VO2) <18 ml/kg/min. Cardio-HKT consisted of a 3 weeks daily in-water training, combined to educational and psycho-behavioural sessions. Patients underwent a six-minute-walking-test (6mWT), a cardiopulmonary exercise test at baseline and after 3 weeks of Cardio- HKT. Quality of life was assessed with the Minnesota Living with Heart Failure Questionnaire (MLHF). Results: All patients completed the Cardio-HKT rehabilitation program without complications. The 6mWT improved from 453±172 m to 571±120 m (p<0.01), peak VO2 from 13.0±3.1 to 14.5±2.9 ml/kg/min (p=0.03), whereas VE/ CO2 slope declined from 37±10 to 33±9 (p=0.01). MLHF markedly improved from 56 (68-27) to 18 (40-7) (p<0.01). Conclusions: Our results support the safety and efficacy of the innovative Cardio-HKT rehabilitation program in patients with advanced HF.